Insights into the Sinful Self: Liturgy and Subject-Formation in Byzantine Christianity (KULT_online, 2015)
With his latest monograph Liturgical Subjects: Christian Ritual, Biblical Narrative, and the Formation of the Self in Byzantium, Derek Krueger provides a detailed study of Christian selfhood in Byzantine Christianity from the sixth to eleventh century. The study traces the development of a certain form of Christian identity in the works of Romanos the Melodist, Andrew of Crete, Theodore the Stoudite and Symeon the New Theologian. By examining liturgical texts like hymns and prayers and their placement within the liturgical calendar, Krueger shows how, through expressions of guilt, repentance, and compunction, Byzantine Christians identified themselves as sinners in need of salvation.